2009
DOI: 10.1088/0022-3727/42/18/185303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of deposition pressure on the adhesion of ZnO thin films deposited by cathodic vacuum arc deposition on polyimide foil substrates

Abstract: ZnO thin films, used as polymer protection layers against ultraviolet radiation and atomic oxygen for space application, were deposited on polyimide foil substrates using a cathodic vacuum arc deposition technique. A fragmentation test was employed to investigate the influence of deposition pressure on the adhesion of ZnO thin films. It was found that all the samples have good adhesive properties. Low deposition pressure is beneficial to the adhesion of ZnO films and polyimide substrates. Scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Deposition pressure has a marked effect on ZnO thin films deposited by this technique on polyimide foil substrates as studied by Changji et al The thin films exhibits good adhesive properties at the low deposition pressure. 230 High deposition rates in the range from 50-500 Å/second have been reported for this deposition process. As this technique also involve the formation of macro-particles with diameters ranging from 0.5 to 50 m along with the atomic and ionic evaporate, appearance, morphology and physical properties are degraded.…”
Section: Cathodic Arc Vapour Deposition Techniquementioning
confidence: 76%
“…Deposition pressure has a marked effect on ZnO thin films deposited by this technique on polyimide foil substrates as studied by Changji et al The thin films exhibits good adhesive properties at the low deposition pressure. 230 High deposition rates in the range from 50-500 Å/second have been reported for this deposition process. As this technique also involve the formation of macro-particles with diameters ranging from 0.5 to 50 m along with the atomic and ionic evaporate, appearance, morphology and physical properties are degraded.…”
Section: Cathodic Arc Vapour Deposition Techniquementioning
confidence: 76%
“…Understanding of the fracture behavior of flexible thin films is known to be complicated with interdependency of the physical parameters such as grain size, roughness, defects, and thickness. For instance, Changji et al 27 and Balakrisnan et al 28 have reported that pores and dislocations in films facilitate crack initiation, while grain boundaries provide an easy path for crack propagation. An extra energy is required for crack propagation if a higher effective density of grain boundary (or smaller grains) is present.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The generation of an electrostatic potential produced by the plasma, and the interaction between metallic plasma and neutral gas, such as elastic collisions and charge-exchange reaction, have a strong influence on the ion energy, and ion flux distribution. For instance, Changji et al [20] found that the energy of Zr (Zirconium) ions arriving at the substrate decreases significantly with the deposition pressure. This effect explains the fact that the adhesion decreases as the deposition pressure increases.…”
Section: Introductionmentioning
confidence: 99%